Answer: [tex]y^2[/tex]
Reason:
A square root represents an exponent of 1/2
So [tex]\sqrt{y} = y^{1/2}[/tex]
Raising that to the fourth power gets us this,
[tex](\sqrt{y})^4 = (y^{1/2})^4\\\\ (\sqrt{y})^4 = y^{(1/2)*4}\\\\ (\sqrt{y})^4 = y^{2}\\\\[/tex]
----------------
Edit: Here's an alternative route
[tex](\sqrt{y})^4 = (\sqrt{y})*(\sqrt{y})*(\sqrt{y})*(\sqrt{y})\\\\ (\sqrt{y})^4 = (\sqrt{y})^2*(\sqrt{y})^2\\\\ (\sqrt{y})^4 = y*y\\\\ (\sqrt{y})^4 = y^2\\\\[/tex]
The first line is possible because raising anything to the 4th power is the same as having 4 copies of it multiplied out (eg: 3^4 = 3*3*3*3 = 81).
Then in the second line, I collected the terms into pairs
By line 3, the square root and squaring exponent cancel each other out. This only works if y is not negative.